Experimental Studies on a Novel Single-Phase Z-Source Inverter for Grid Connection of Renewable Energy Sources - Rajakaruna, Sumedha (University of New South Wales, 2008)
In order to supply power from a photovoltaic array or a fuel cell stack at a low dc voltage to a grid at a high ac voltage, a power conditioning unit capable of both voltage-boosting and inversion is required. Newly introduced Z-Source inverter is capable of achieving both these objectives by a single converterstage. This paper describes how a single-phase Z-Source inverter can be built for grid-connection of a photovoltaic array. Significant changes are needed in sizing the components and generating switching signals. Results of experimental investigations performed on a laboratory prototype are presented.